Water Security for Palestinians and Israelis : Towards a New Cooperation in Middle East Water Resources /: Towards a New Cooperation in Middle East Water Resources. (2021) - Ward, Christopher; Learmont, Isabelle; Ruckstuhl, Sandra
No abstract available